2012
DOI: 10.1371/journal.pone.0043264
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Quantity and Quality of Light on Photosynthetic Periodicity in Coral Endosymbiotic Algae

Abstract: Symbiotic corals, which are benthic organisms intimately linked with their environment, have evolved many ways to deal with fluctuations in the local marine environment. One possible coping mechanism is the endogenous circadian clock, which is characterized as free running, maintaining a ∼24 h periodicity of circuits under constant stimuli or in the absence of external cues. The quantity and quality of light were found to be the most influential factors governing the endogenous clock for plants and algae. Unic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
(67 reference statements)
1
30
0
Order By: Relevance
“…Thus, the rhythmicity was maintaining daily oscillations with a free-run cycle when conditions switched from LD cycles to LL conditions. The rhythms of photosynthesis in Symbiodinium show circadian pattern and fulfil the three characteristics thereof: first, the rhythm is kept under constant conditions of light; second, light can entrain the rhythm, whereas different light spectrums change the entrainment of the cycle [40]; and third, our former work shows the ability of Symbiodinium in culture as well as inside the coral tissue to compensate for temperature changes and maintain the rhythm under LD and LL [41]. The LL free-run period presented here differs from the LD period mainly in the magnitude of the oxygen evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rhythmicity was maintaining daily oscillations with a free-run cycle when conditions switched from LD cycles to LL conditions. The rhythms of photosynthesis in Symbiodinium show circadian pattern and fulfil the three characteristics thereof: first, the rhythm is kept under constant conditions of light; second, light can entrain the rhythm, whereas different light spectrums change the entrainment of the cycle [40]; and third, our former work shows the ability of Symbiodinium in culture as well as inside the coral tissue to compensate for temperature changes and maintain the rhythm under LD and LL [41]. The LL free-run period presented here differs from the LD period mainly in the magnitude of the oxygen evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The actin gene is highly expressed and conserved in dinoflagellates (Kim et al, 2011). This gene and other HKGs have already been successfully applied as a reference, together with other HKGs, in several recent gene expression studies of different Symbiodinium clades, because of their stable expression during stress exposure (Rosic et al, 2011b;McGinley et al, 2012;Sorek and Levy, 2012;Ogawa et al, 2013). Furthermore, photosynthesis-related transcripts were recognized as shared among the clades and included genes such as Ribulose-1,5-bisphosphate carboxylase oxygenase (Rubisco) and peridinin-chlorophyll a-binding protein that are unique to dinoflagellates (Rowan et al, 1996;Leggat et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In hospite reduction of blue light is a function of host filtering and shifting of spectra via fluorescent proteins (Leutenegger et al, 2007;Quick et al, 2018;Salih et al, 2000;Smith et al, 2013), resulting in an order of magnitude reduction in the amount of blue light transmitted to deeper tissue layers in corals (Lichtenberg, Larkum, & Kühl, 2016). Sorek and Levy (2012) showed that blue light spectra increased mRNA expression of free-living Symiodiniaceae cryptochromes CRY1 and CRY2, but were downregulated when hosted in the coral Stylophora pistillata. Though an E. pallida host GFP has not yet been identified, they exhibit patterns of green autofluorescence when excited by blue light , which could reduce the amount of blue light transmitted to endosymbionts.…”
Section: In Hospite Disruption Of Blue Light Photoreceptionmentioning
confidence: 99%